Nicotinic Acetylcholine Receptor Modulation Distinguishes Clinical Benefits of Galantamine in Alzheimer’s Disease - Pavel V. Svintozelskiy; Andrew J. Wahlert; Carson Harrod; Denis G. Kay; Kurt P. Grady; George T. Grossberg (Sage Open Aging, 2026)
Alzheimer’s disease (AD) is the leading cause of dementia and represents a public health challenge in aging populations. Acetylcholinesterase inhibitors (AChEIs) remain first-line symptomatic therapy for mild to moderate AD, with real-world effectiveness largely influenced by tolerability, adherence, and treatment persistence. Galantamine and its inactive prodrug benzgalantamine are differentiated within the class by a dual mechanism that combines reversible acetylcholinesterase inhibition with positive allosteric modulation of nicotinic acetylcholine receptors. This narrative review synthesizes preclinical and clinical evidence examining galantamine-based therapy, with a focus on aspects related to nicotinic acetylcholine receptors: behavioral symptoms and sleep-related effects. Across randomized, observational, and longitudinal studies, galantamine has been associated with improvement or stabilization in behavioral domains including aberrant motor behavior, agitation/aggression, anxiety, apathy, delusions, disinhibition, and hallucinations. However, like other members of the AChEI class, gastrointestinal tolerability issues may affect treatment persistence. Benzgalantamine was developed to address gastrointestinal tolerability, with the aim of improving adherence and long-term treatment continuity.